Assessment of the physical health of students of middle and upper grades - Bakiko, Ihor; Savchuk, Sergey; Dmitruk, Vitali; Radchenko, Оleksandr; Nikolaev, Sergey (Journal of Physical Education and Sport, 2020)
Formulation of the problem.The problem of deterioration of the physical health of the population of Ukraine, and especially of the younger generation, remains urgent. In recent years, the health of children and adolescents is considered critical by professionals. According to them, one of the main reasons for this situation is the decrease in motor activity of students, which is progressing every year. At the same Krutsevich T. Yu. N. V. Moskalenko and others point out that the current system of physical education in secondary schools does not reach its goal - to strengthen the health of students, as there is an increase in children with chronic diseases. Therefore, the urgent issue of the theory and practice of physical education is the search for innovative technologies for the organization of physical education in general educational institutions, which will help preserve and enhance the physical health of students. Approach. Analysis of scientific and methodological literature, express assessment of the level of physical health, methods of mathematical statistics. Purpose. The work was to determine the level of physical health of pupils of the 5th - 11th grades. Result: The research conducted gave grounds to establish that the level of physical health of schoolchildren by all features is low or lower than the average and during the studies in secondary school is deteriorating. The forecasted index of physical condition declined Conclusions: therefore, in the course of the study, the level of physical health of boys and girls of the 5th - 11th grades was determined. It was found that 44.8% of boys have a low level of physical health, 27.0% are below the average and 28.2% have an average. Among the surveyed girls, 29.8% have a low level of physical health, 37.2% are below the average, 33.0% of girls who participated in the study, the level of physical health is average.
Keywords: schoolchildren; health; anthropometric measurements; physical development; age standards